Studi Literatur Model Pembelajaran POGIL untuk Meningkatkan Hasil Belajar Peserta Didik pada Pembelajaran Kimia - Vini Wahyuni Putri; Fauzana Gazali (Ranah Research : Journal of Multidisciplinary Research and Development, 2021)
Chemistry learning has abstract concepts and mathematical concepts that give rise to misconceptions in students. This study aims to obtain an overview of the application of the POGIL model in improving student learning outcomes. This type of research is library research with descriptive analysis. The data used is secondary data, namely scientific journals in the form of articles. The data collection method in this study is the documentation method with data analysis techniques by Miles and Huberman, namely data reduction (reduction), data presentation (display), and conclusions (conclusion drawing). The results of the study show that learning using the POGIL model in chemistry learning can improve student learning outcomes.